Diversity and Distribution of Annual Dicotyledonous Weeds in Peanut (Arachis hypogaea L.) Agrocenoses - Turdieva Nilufar Mo‘minovna (American Journal of Biodiversity, 2026)
This article analyzes the biological and morphological characteristics of annual dicotyledonous weed species occurring in peanut yeryong‘oq (Arachis hypogaea L.) fields. The study reveals that these weeds are characterized by rapid germination, high seed productivity, and strong ecological adaptability, which negatively affect crop development. It was also shown that their distribution and competitiveness in agrocenoses directly reduce peanut yield. The article highlights the agro-technical importance of identifying and controlling these weed species.